Measuring parameters of the deuteron beams in experiments with the target assembly QUINTA using solid-state track detectors - Husak, K.V.; Artiushenko, M.Yu.; Zhuk, I.V.; Bukhal, O.V.; Sotnikov, V.V.; Voronko, V.A.; Safronava, A.A.; Patapenka, A.S.; Tyutyunnikov, S.I.; Furman, W.I.; Kadykov, M.G.; Chilap, V.V.; et al. (Вопросы атомной науки и техники, 2014)
The results of measurements of the deuteron beams parameters with energies of 1, 4 and 8 GeV at the irradiation of the uranium subcritical assembly "QUINTA" are presented. The data obtained on the incident beam position relative to the axis of the target and on the real geometric parameters of the beam allow one to analyze correctly the spatial distribution of reaction rates within the target assembly and compare these measured in different irradiation runs as well as to simulate experiments by such codes as MCNPX, GEANT4, FLUKA et al. The investigation has been performed at the V.I. Veksler and A.M. Baldin Laboratory of High Energy Physics, JINR.